Dakwah Mimbar dan Transformasi Pola Komunikasi Keagamaan di Era Digital (Studi di Kota Lhokseumawe) - Muhajir Al-Fairusy; M. Rizal Fazri.Ar; Ismuhar (Journal of Social and Policy Issues, 2026)
The development of digital technology has fundamentally changed the religious communication patterns of Muslims, including the practice of pulpit preaching, which has long been understood as an authoritative and sacred space for religious communication. This study aims to analyze the transformation of congregational communication patterns in receiving pulpit preaching in the digital era and examine how the position of the pulpit is reconstructed in relation to new media. This study uses a descriptive qualitative approach with data collection techniques such as in-depth interviews, participant observation, and documentation, conducted in several large mosques in Lhokseumawe City. The results show that pulpit preaching is still maintained as a source of religious legitimacy, especially among adults and the elderly. However, the younger generation tends to combine physical presence in the mosque with the consumption of digital preaching through social media platforms. A key finding of this study is the emergence of a hybrid communication pattern, namely the integration of oral preaching from the pulpit with the distribution and amplification of messages through digital media. This pattern marks a shift in preaching from one-way communication to multi-channel dialogic communication that is participatory and interactive. Theoretically, this research enriches Islamic communication studies by integrating a transactional communication approach and uses and gratifications theory in the context of contemporary da'wah. Practically, these findings emphasize the importance of digital literacy for preachers and da'wah institutions to ensure that da'wah from the pulpit remains relevant, has broad reach, and fosters community engagement in a digital society.